IbM Penyulingan Minyak Kayu Putih dan Briket Arang di Desa Delo dan Raekore - Dedy Nataniel Ully; Bernadus Wuwur (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2018)
Villagers of Delo and Raekore have a traditional eucalyptus refining business by boiling the eucalyptus leaves for aromatic oils. Eucalyptus oil produced quite well, it's just a long distillation process that is 5 to 6 hours so it requires a lot of wood. While the availability of firewood in the forest is currently quite difficult, so people often cut down trees in the forest. So need to find a solution by changing the way of boiling by steam method and using charcoal  fuel made from coconut shell, because it has a higher calorific value than the shell is burned directly. Traditional refined eucalyptus oil products, ranging from 2 to 3 beer bottles   (1 bottle of beer = 350 ml) per day, so that through the activities of IbM can apply the appropriate technology products that is the installation of wood crude oil refinery by steam method and the using of briquette fuel. The steamed container produced has a volume of 160 liters while the charcoal briquette printing device is capable of printing 8 charcoal briquettes in one print. The using of refinery installations by steam method and charcoal charcoal fuel, can increase the production capacity of eucalyptus oil  to encourage economic improvement of Delo and Raekore villagers. The eucalyptus refining oil refinery has a production capacity of 4 to 5 bottles of beer (1 bottle of beer = 350 ml) per day and charcoal briquette presses have a production capacity of 8 charcoal briquettes.